Assessment and management of asthma in an accident and emergency department. Issue 12 (December 1985) - Reed, S; Diggle, S; Cushley, M J; Sleet, R A; Tattersfield, A E
Abstract : Patients with asthma presenting to the accident and emergency department at Southampton General Hospital during 12 months were reviewed retrospectively to determine how many patients attended, when and how patients were assessed and treated, and what factors appeared to influence whether a patient was admitted to a medical ward or not. Thirty five visits were made by patients requesting a repeat prescription for a metered dose inhaler. A further 193 visits were made by 152 patients (93 male, 59 female); only data on the first visit of any individual were analysed in this study. Patients were more likely to visit in the autumn, at the weekend, and in the evenings. Observations and measurements used to assess the severity of asthma were recorded with variable frequency–heart rate in 84% of examinations, pulsus paradoxus in 13%, and peak flow rate in 11%. Blood pressure was five times more likely to be recorded than peak flow rate. The drugs used to treat asthma were, in order of frequency, a beta agonist (120 patients), intravenous aminophylline (39), and intravenous corticosteroids (30). Sixty (39%) of the patients were admitted to a medical ward. Admission was more likely to occur when patients arrived during the week than at the weekend, when they had cyanosis or pulsus paradoxus, and after receiving parenteral treatment. There was no difference in mean heart rate between patients admitted to the ward and those discharged home. Although there was no specific evidence of inappropriate admission to or discharge from hospital in this retrospective study, the failure to record more objective measurements of the severity of asthma and, in particular, the extent of the airflow obstruction, is cause for concern.